Analysis of Sports Facilities and Infrastructure for Academic Achievement of UMJ Sports Education Students - Mulyanto, Taufik Yudi; Ishaq Gery, Muhammad; Yulisatria, Guntur; W, Anugrah Tegar (Jurnal Pendidikan Jasmani (JPJ), 2024)
This study aims to see how much the influence of facilities and infrastructure affects the academic achievement of sports education students at Muhammadiyah University Jakarta. The indicator taken is an analysis of the facilities and infrastructure used for sports practice lectures. From these indicators it can be seen that what causes an increase or decrease in student academic achievement. This research uses quantitative methods on sports education students at Muhammadiyah University Jakarta. This research has an output target, namely the analysis of facilities and infrastructure that will be published in research journals.